Kajian Karakteristik Pedagang Kaki Lima Sempol Ayam : Study of the Characteristics of Chicken Sempol Street Vendors - Azzis, Muhammad; Mudawaroch, Roisu Eny; Rinawidiastuti, Rinawidiastuti (Jurnal Riset Agribisnis dan Peternakan, 2022)
The purpose of this study was to determine the characteristics of broiler traders in Purworejo Regency. The method used in this research is descriptive analysis method. The characteristics of sempol traders are that 58.2% are male and 12.7% live in Kutoarjo. The total length of business for chicken sempol traders is 1-5 years and only 96.4% sell chicken sempol. 76.4% of self-managed businesses with a seed price of IDR 1000 is 92.7%. The production of chicken sempol which was not sold immediately was 83.6% and if it was not sold as much as 87.3% would be stored for sale the next day. How to store it in the refrigerator (100%). Serving characteristics, sempol merchandise is sold on cart racks as much as 100%, includes 100% merchandise and is packaged using plastic. 89.1% of the sempol traders brought their own buckets and 56.4% filled them with water brought from home. 89.1% of chicken traders who carry and use dishwashing soap for Chicken Sempol traders wash their hands when the respondent’s hands are dirty (100%) and the cart is clean by 54.5%.